The renin-angiotensin system in the esophageal mucosa of healthy subjects and patients with reflux disease - Björkman, Eleonora; Edebo, Anders; Casselbrant, Anna; Helander, Herbert F.; Bratlie, Svein Olav; Vieth, Michael; Fändriks, Lars (Scandinavian Journal of Gastroenterology, 2013)
Objective. Components of the renin-angiotensin system (RAS) were recently discovered in the esophagus, which could be of interest in relation to gastroesophageal reflux disease (GERD). The present study was undertaken to confirm and further investigate the expression of RAS in healthy and refluxed exposed human esophageal mucosae. Methods. Esophageal biopsies were obtained from healthy subjects (n = 34) and individuals with erosive reflux disease (ERD, n = 28). Evaluation of general morphology and histological signs of reflux as well as investigation of gene transcript, protein expression and localization of various RAS components using RT-PCR, ELISA, western blot and immunohistochemistry were performed. Physiological effects of the AT2R were investigated in Ussing chamber experiments. Results. The study confirmed histological signs of reflux in ERD and expression of ACE, AT1R, AT2R and CatD in all examined specimens. In addition, the main effector peptide AngII, the pro-hormone AGT, the Mas receptor and the angiotensin-forming enzymes renin, CMA, CatG and NEP were present. Individuals with reflux disease had higher transcription activity of ACE and AT1R, increased protein levels of AT2R and lower levels of MasR. AT2R stimulation increased the ion currents in healthy epithelium, whereas epithelium from individuals with reflux disease exhibited no significant response. Conclusions. The study demonstrated that a local RAS is present in the human esophageal epithelium. Some RAS components were significantly altered in individuals diagnosed with ERD suggesting involvement in the pathophysiology of GERD. © 2013 Informa Healthcare.
CRIS-Team Scopus Importer:2025-03-05
Keywords: Angiotensin II type 2 receptor; Gastroesophageal reflux disease; Human esophageal mucosa; Renin-angiotensin system; Ussing chamber